Seasonal variation in coumarin content of Mikania glomerata - Pereira, Ana Maria Soares [UNESP]; Câmara, Francisco Luiz Araújo [UNESP]; Ghini, Raquel [UNESP]; Vilegas, J. H Y; Lancas, F. M.; Franca, S. C. (My University, 2000)
Mikania glomerata Spengal extract contains approximately 0.5 percent of coumarin, a substance that displays anti-inflammatory and expectoratory activities. Extracts from different young leaves of plants collected during the early evening of December and July contained the highest levels coumarin. Plants dried in oven with circulating air contained 7.3 mg of coumarin/g of dry weight, demonstrating that this was the most appropriate drying condition for Mikania glomerata.
Keywords: Argentina; Drying; Guaco; Harvest; Medicinal plant; Phenol metabolism; coumarin; expectorant agent; Mikania glomerata extract; phenol; plant extract; unclassified drug; agriculture; antiinflammatory activity; heat treatment; metabolism; nonhuman; plant leaf; seasonal variation; weight; Mikania; Mikania congesta; Mikania glomerata